Efektivitas Zat Aktif Fipronil pada Berbagai Substrat Fagostimulan untuk Pengendalian Kecoak Jerman (Blattella germanica L.) - Maula, Riska Isna; Pratiknyo, Hery; Susilo, Untung; Ambarningrum, Trisnowati Budi (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
German cockroach (Blattella germanica L.), is a residential insect pest and vector of various diseases. To control its population, alternative chemical control models with Fipronil 0.03% are now being developed. Fipronil has been proven to be effective and has no resistance. To increase the effectiveness of the bait in controlling German cockroaches, a fipronil 0.03% combination needs to be developed with a phagostimulant bait of bananas, durian, erythisol sugar, and sugar formulation, so this study needs to be done. This study used an experimental method with a randomized block design (RBD), five treatments such as A: bait with a combination of banana phagostimulant and 0.03% fipronil, B: bait with a combination of durian phagostimulant and 0.03% fipronil, C: bait with a combination erythisol phagostimulant and 0.03% fipronil, D: bait with a combination of sugar phagostimulant and 0.03% fipronil, K: bait with a combination of matrix and fipronil 0.03% (control positive) was used for the interest test, and bait with a matrix without fipronil 0.03% (control negative) was used for mortality testing. The observations the average results for durian, banana, sugar formulated, erytrisol sugar and controls, respectively 20%, 20%, 21.6%, 12.4%, and 22.8%, while the results bait consumed with durian stimulation are 0.29g, banana 0.31g, sugar formulation 0.28g, erytrisol sugar 0.26g and control 0.24g. However, based on statistical tests, the results of the interest test with the feed consumption test between treatments showed no significant difference (p>0.05). The test results in mortality of cockroaches Germany's feed with phagostimulan durian, banana, formulations sugar, sugar erytrisol and control consecutively 98% 100 %, 98%, 98%, and 20%, based on the statistical test there is a significant difference (p<0.05), where the difference based on the Duncan test is their treatment compared to control.